MENINGKATKAN KECERDASAN INTERPERSONAL ANAK USIA DINI MELALUI KEGIATAN BERMAIN - Ilahi, Zaitun Nur Rizqi; Elvira, Melly (Jurnal Penelitian Anak Usia Dini, 2024)
Interpersonal intelligence has an important role in children's social development. Children who have good interpersonal intelligence will easily adapt to new environments. This research aims to determine the increase in interpersonal intelligence of children aged 5-6 years through role playing activities. This research uses a quantitative approach of the Quasi Experiment type with an equivalent time series design. The sample in this study was the B2 group of Almaarif Singosari Islamic Kindergarten, totaling 16 children. The data collection technique used is observation and documentation, while the data analysis technique uses the Friedman Test. Based on the research results, data analysis carried out using the Friedman test showed that the p value was <.001, which means there was a significant difference in each posttest carried out. The results of the Friedman test calculation show that the p value (<.001) <0.05 means Ha is accepted and Ho is rejected. Therefore, it can be concluded that role playing activities can improve interpersonal intelligence in children aged 5-6 years at Al Maarif Singosari Islamic Kindergarten.